Optimal control of a batch fermentation process with nonlinear time-delay and free terminal time and cost sensitivity constraint. (August 2016) - Yuan, Jinlong; Liu, Chongyang; Zhang, Xu; Xie, Jun; Feng, Enmin; Yin, Hongchao; Xiu, Zhilong
Abstract : Highlights: An control problem is proposed to maximize the productivity of 1, 3-PD. The problem with free terminal time is transformed via a hybrid time-scaling strategy. A parallel algorithm is proposed to solve the problem. We consider a cost sensitivity constraint to reflect operational requirements. Abstract: In this paper, we consider a nonlinear time-delay dynamic system with uncertain system parameters to characterize the process of batch fermentation. Our goal is to design an optimal control scheme to maximize the productivity of 1, 3-propanediol (1, 3-PD). Accordingly, we introduce an optimal control problem governed by the nonlinear time-delay dynamic system, in which the control variables are the free terminal time of the batch fermentation process and the initial concentrations of biomass and glycerol. The optimal control problem is subject to a cost sensitivity constraint for ensuring that an acceptable level of the system performance is achieved and continuous state inequality constraints for ensuring that the concentrations of biomass, glycerol, 1, 3-PD, acetate, ethanol lie within specified limits. Then, the optimal control problem with free terminal time is transformed, via a hybrid time-scaling strategy, into an equivalent problem with fixed terminal time, which is much preferred for numerical computation. Using the constraint transcription and local smoothing approximation techniques, we approximate these continuous state inequality constraints by conventional inequality constraints to yield an approximate optimal control problem. Because of the highly complex nature of this approximate problem, a parallel algorithm based on the filled function method is constructed to solve this approximate problem. Finally, it is observed that the optimal control obtained is satisfactory through numerical simulations.